Mediating effects of job satisfaction on relationship between distributed leadership, entrepreneurial leadership and organizational commitment among secondary school teachers in Peninsular Malaysia - Zulkiefli, Siti Aminah (2022)
The purpose of this study is to investigate the mediating effect of job satisfaction on the relationship between distributed leadership, entrepreneurial leadership and organizational commitment among secondary school teachers in Peninsular Malaysia. Professional development among teachers is increasingly critical due to the high number of workload in school; extracurricular management, clerical work, and engaging with parents and communities. This study was designed as a quantitative correlational study using the survey method of data collection. A set of instruments consisting of five assessment parts with 151 questions by Three-Dimensional Model (TCM), Distributed Leadership Readiness Scale (DLRS), Entrepreneurial Leadership Questionnaire (ELQ), and Job Satisfaction Survey (JSS) are utilized for the study to 350 respondents. Descriptive, inferential analysis, and structural equation modeling were used to elaborate the collected data. The result shows that organizational commitment is at a moderate level meanwhile distributed leadership, entrepreneurial leadership and job satisfaction are at high level. Only gender shows no significant difference in organizational commitment while age and length of service show significant differences in organizational commitment. The result indicated that there is a significant relationship between organizational commitment, distributed leadership, entrepreneurial leadership and job satisfaction. Structural equation modeling (SEM) analysis by using bootstrapping shows that distributed leadership has a partial mediation effect on organizational commitment and no mediation effect on entrepreneurial leadership. The result of SEM indicated that distributed leadership, entrepreneurial leadership, and job satisfaction managed to estimate 43% of variance in organizational commitment. The findings of this study strengthen the understanding the importance of distributed and entrepreneurial leadership towards organizational commitment in presence of job satisfaction as a mediator. This study contributed to some recommendations for practice, theory, and future research to improve the level of organizational commitment in presence of distributed leadership, entrepreneurial leadership and job satisfaction as mediator.